Improving Mathematics Learning Outcomes in Fractional Materials Through Audio-visual Media for Fifth Grade Students SDN Muktiharjo Kidul 04 - Astuti, Tri Widya (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The learning process does not only involve students directly but needs to use learning support tools. The researcher examines whether audio-visual media can improve the mathematics learning outcomes of fractions in fifth grade students of SD Negeri Muktiharjo Kidul 04. This research uses Classroom Action Research (CAR). Data analysis was carried out by calculating the achievement of student learning scores in each cycle based on KKM. The results of the study can be seen in the increase in student learning outcomes, from the results of the cycle 1 value shows an average of 60.54 with the percentage of students who complete the individual KKM 62.17%. While in cycle 2 it shows an average of 70.27 with a complete percentage of individual KKM 83,78%. This shows that audio-visual media can improve student learning outcomes in mathematics in class V SD Negeri Muktiharjo Kidul 04 Pedurungan District, Semarang City, Academic Year 2020/2021.